Construction of A Self-Actualization Measurement Instrument Based on Abraham Maslow's Theory - Mohammad Akhtar Fakhri Adjie; Anisa Nurjanah; Azzahra, Fatiya; Wafi Nadiah Rahmawati; Pramudita Hera Wirdatama; Novita Sari (Cattleya Darmaya Fortuna, 2026)
The primary focus of humanistic psychology is the development of human potential toward self-maturity. This study aims to develop and test the psychometric properties of a self-actualization measurement tool constructed based on the fifteen characteristics of self-actualization from Abraham Maslow's theory. Data were collected online from 200 early adult participants (aged 17-30 years) using a convenience sampling technique. Data analysis was performed using JASP software through internal consistency reliability testing and Confirmatory Factor Analysis (CFA) to test construct validity. The analysis results showed that this 32-item instrument has adequate discriminatory power. The reliability test produced a Cronbach's Alpha value of 0.93, indicating a very high level of internal consistency. Construct validity testing through CFA showed the model has a very good fit with the empirical data, indicated by a chi-square value of 458.522 (p = 0.060), a CFI of 0.986, an RMSEA of 0.023, and a SRMR of 0.043. Unlike previous instruments that measured related designs, this study directly operationalized Maslow's fifteen characteristics of self-actualization and empirically tested their structural integration using contemporary psychometric standards. These findings support a unidimensional structure, strengthening the empirical foundation of classical humanistic theory within a modern quantitative framework. Based on these results, this measuring instrument was found to be empirically valid and reliable for measuring the psychological dimensions of self-actualization. This instrument is suitable for use as an assessment tool in self-development programs and counseling services to help individuals identify their potential and guide their personal growth.